Activation students’ interest to practice at the piano - Заря, Л. О. (Scientific notes of the pedagogical department, 2017)
The article discusses the possibilities of the piano teacher’s work the development ofstudents' interest in the piano. It was specified that theconsciousness of students, isalways connected with emotions and feelings.Same considers the psychological peculiarities of comprehensive training, development, formation of skills of the piano students in the system of teacher training of musical arts secondary school, music Director of a preschool children institution. The author considers the problem of development of interest to the piano in connection with psychologicaland pedagogical work of a teacher of special piano. Recommended Certain forms ofwork with students, are recommended which takes into account the development of psychological factors of interest, such as perception, attention, thinking, memory, emotion.